GOOD GOVERNANCE VS SHADOW STATE DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH - Syarif Hidayat; Abdul Malik Gismar (Pusat Penelitian Politik, 2010)
Good governance is crucialfor the attainment of development goals and delivering the promises of democracy However it cannot be understood apart from the political regime and the political dynamic within whichit exists Hence establishing good governance in a transitional democracy such as Indonesia has its additionalchallenges This article attempts to elucidate this issue Specifically it attempts to show that currently low qualityofgovernance in provinces accross Indonesia might be linked to the existence ofshadow state Illustrations aregiven both from quantitative analysis drawn from the results of Partnership Governance Index and qualitativestudies in six provinces